2020
DOI: 10.1007/s00784-020-03461-8
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of soft tissue volume at pontic sites: a comparison between a cross-linked and a non-cross-linked collagen matrix

Abstract: Aim To assess histopathological and histomorphometric outcomes of soft tissue volume augmentation procedures at pontic sites using a volume-stable cross-linked collagen matrix (VCMX) and a non-cross-linked collagen matrix (XCM). Materials and methods In twelve adult beagle dogs, the mandibular premolars and first molar were hemisected and the mesial root extracted. Soft tissue augmentation was randomly performed using VCMX, XCM, or a sham-operated control. Sacrifice was performed after 4, 8, and 26 weeks. Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Nevertheless, the present study confirms existing evidence for the possibility of new bone formation within the VSCM, thus confirming and extending the first reports showing little bone formation inside the VSCM in a dog model [15,16]. VSCM was also reported to be encapsulated by soft tissue without any evidence of mineralization [15,34]. Consistent with the previous observations, VSCM is not an ideal material to support bone formation and might be developed towards a biomaterial supporting chondrogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the present study confirms existing evidence for the possibility of new bone formation within the VSCM, thus confirming and extending the first reports showing little bone formation inside the VSCM in a dog model [15,16]. VSCM was also reported to be encapsulated by soft tissue without any evidence of mineralization [15,34]. Consistent with the previous observations, VSCM is not an ideal material to support bone formation and might be developed towards a biomaterial supporting chondrogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…The functionalized collagen matrix used in this clinical case intends to mimic the natural extracellular matrix of a connective tissue graft, providing a niche for host cells during healing [ 23 , 24 ], which allows cell migration, adhesion, and differentiation, as well as supporting vascular proliferation. Moreover, it has been suggested that the volume-stable collagen matrix has long-term dimensional stability due to its low level of cross-linking degradation [ 25 ]. An in vitro study showed that i-PRF induced cell migration and increased the gene expression of TGF- β mRNA, platelet-derived growth factor (PDGF), and collagen type I [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both substitutes have a favourable effect and are accompanied by a lower morbidity. VCMX seems even to be more promising than XCM as the latter degrades earlier than VCMX (Moraschini et al., 2020; Naenni et al., 2020). These substitute materials may be suitable for sites, which only require minor thickening of the mucosa, for patients who are pain‐sensitive and for patients who do not consent to the harvesting of soft tissues (Lissek et al., 2020).…”
Section: Discussionmentioning
confidence: 99%